2020
DOI: 10.1144/m51-2019-33
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 1 Introduction to New Caledonia: geology, geodynamic evolution and mineral resources

Abstract: This Memoir summarizes our current knowledge of New Caledonia geology, geodynamics and mineral resources based on published and unpublished information. Except for a short paper timed for the 34th International Geological Congress (Cluzel et al. 2012b), there has been no review of the geology of New Caledonia since Paris (1981)that is, for more than 35 years. As such, it is timely that this Memoir is published.This Memoir comprises a collection of ten self-contained chapters written by 28 researchers from New … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 91 publications
1
16
0
Order By: Relevance
“…The southwest Pacific area went through a complex tectonic and paleogeographic evolution during the Eocene, related to the inception of the Tonga-Kermadec subduction system (recent reviews can be found in Cluzel et al, 2012;Collot et al, 2020;Dallanave et al, 2018b, Dallanave et al, 2020Maurizot et al, 2020a, Maurizot et al, 2020bSutherland et al, 2020). The Tonga-Kermadec subduction initiated in the middle Eocene immediately to the east of the Norfolk Ridge, the northernmost part of which is The eigenvector are oriented as the average eigenvector of the anisotropy of magnetic susceptibility (AMS), shown in Figure 8B.…”
Section: Paleogeographic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The southwest Pacific area went through a complex tectonic and paleogeographic evolution during the Eocene, related to the inception of the Tonga-Kermadec subduction system (recent reviews can be found in Cluzel et al, 2012;Collot et al, 2020;Dallanave et al, 2018b, Dallanave et al, 2020Maurizot et al, 2020a, Maurizot et al, 2020bSutherland et al, 2020). The Tonga-Kermadec subduction initiated in the middle Eocene immediately to the east of the Norfolk Ridge, the northernmost part of which is The eigenvector are oriented as the average eigenvector of the anisotropy of magnetic susceptibility (AMS), shown in Figure 8B.…”
Section: Paleogeographic Implicationsmentioning
confidence: 99%
“…The complete sets of directions are given in supporting Supplementary Table S2 available online. emerging to form the New Caledonia archipelagos ( Figures 7C). The history of the eastern margin of northern Zealandia before the Tonga-Kermadec subduction is still debated, because the geology of New Caledonia suggests the presence of a pre-Tonga east-dipping subduction zone (Cluzel et al, 2012;Collot et al, 2020;Maurizot, 2011;Maurizot et al, 2020a, Maurizot et al, 2020b, which is, however, difficult to reconcile with the geologic history derived from seismic profiles acquired in the Tasman area (Sutherland et al, 2017). Zealandia is separated from continental Australia by the oceanic crust of the Tasman Ocean basin, which ended its spreading activity during magnetic anomaly 24 in the early Eocene (∼53 Ma; Gaina et al, 1998;Figures 7C).…”
Section: Paleogeographic Implicationsmentioning
confidence: 99%
“…The obduction of the peridotite layer on sedimentary formations and the basaltic unit of Poya is attributed to the Late Eocene [28][29][30][31][32]. Originally covering a large part of Grande-Terre in New-Caledonia, the formation was gradually stripped by a succession of episodes of chemical and mechanical alteration.…”
Section: Geological Settingmentioning
confidence: 99%
“…For detailed explanation and references regarding the datasets (c-e) see Supplementary Note 1 and Supplementary Tables 1 and 2. Simplified cross sections showing the structure of the Oman 13 (a) and New Caledonia 56,57 (b) ophiolites and their structural relationship to the underlying continental rocks. The far-travelled ophiolite sheets are separated from their oceanic root by exhumed continental units, which show a transition from non-metamorphic to high metamorphic grade.…”
mentioning
confidence: 99%